Introducing winescape attributes to the dual mediation model: a conceptual paper on wine destination websites - Quintal, Vanessa; Phau, Ian; Mastaglia, Aymee (Detay Anatolia Akademik Yayincilik Danismanlik Org. Turz. Ltd, 2012)
Internet websites that emerged in the late 1990s have provided distinct advantages in developing cognitive image, persuading and changing attitude toward a destination that influence travel intention. This conceptual paper has two aims. First, it examines the cognitive communication process of wine destination websites with the dual mediation model (DMM). Second, it introduces the DMM to a new and empirically tested winescape framework that encapsulates the wine destination experience. Notionally, this adds a wine tourism context to DMM theory that is frequently cited in marketing communications literature. Practically, such a study can help wine destination managers to evaluate the persuasiveness of their websites, identify top performing websites for benchmarking and assess how elements of the website impact on intention to travel.